Artificial Intelligence in Nuclear Energy: Legal Challenges and International Cooperation in the Search of Approaches to Regulation - Lev R. Klebanov; Marina S. Lizikova (RUDN Journal of Law)
The application of artificial intelligence (AI) holds the potential for revolutionary advancements in civil nuclear energy. However, this necessitates establishing a framework to ensure the safe and reliable use of AI technologies within the nuclear sector. Law plays a crucial role in adapting existing regulation and developing innovative approaches, concepts and legal structures. This study aims to identify potential threats from the use of AI in nuclear energy and the associated legal challenges, including those related to the nuclear non-proliferation regime and the IAEA safeguards system. It also examines the liability regime for nuclear damage caused by AI at nuclear power plants, insurance considerations, and the activities of the IAEA and other international organizations in exploring AI’s potential to accelerate technological development in nuclear energy and to establish a suitable international regulatory environment. The study further characterizes the current state of international cooperation in this area. The research methodology incorporates formal-legal, comparative-legal, and historical methods, as well as forecasting techniques. The study concludes that the development of principles and standards for the safe use of AI in nuclear energy will initially occur through cooperation among individual states, where the formation of a political space is already underway. Therefore, it is crucial for Russia to leverage this experience and create opportunities for collective cooperation (for example, within BRICS and BRICS+) to regulate AI in the nuclear energy sector.